This Corner of Canaan : Essays on Texas in Honor of Randolph B. Campbell - McCaslin, Richard B. (Book collections on Project MUSE., 2013)
Randolph B. "Mike" Campbell has spent the better part of the last five decades helping Texans rediscover their history, producing a stream of definitive works on the social, political, and economic structures of the Texas past. Through meticulous research and terrific prose, Campbell's collective work has fundamentally remade how historians understand Texan identity and the state's southern heritage, as well as our understanding of such contentious issues as slavery, westward expansion, and Reconstruction. Campbell's pioneering work in local and county records has defined the model for grassro.